Singing Spaces: Fractal Geometries in Cole Swensen's "Oh." - Keller, Lynn (Journal of Modern Literature)
Cole Swensen's homage to opera, "Oh," opens with the word scale; this essay examines how scale figures in the thinking about art performed by the volume. The minimalism of "Oh" refigures the extravagant grandeur of opera, as part of Swensen's rethinking of scale. Swensen uses the lens of fractal geometry to conduct a "respacialization" of the page through which she reconceives the capabilities of lyric and the potential for a rearticulation of the feminine offered by the space of the poem's page. Building upon the examples of Anne-Marie Albiach and Susan Howe, Swensen approaches page space as a potential realm of especially female transgressive and transformative motion, and as the dimension of innovative possibility. The essay proposes and enacts a model of "fractal reading" that enhances understanding of the motion and the transformations of scale in "Oh"—a model that will illuminate other contemporary avant garde texts as well.